2017
DOI: 10.1208/s12248-017-0058-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling a Composite Score in Parkinson’s Disease Using Item Response Theory

Abstract: Abstract.In the current work, we present the methodology for development of an Item Response Theory model within a non-linear mixed effects framework to characterize the longitudinal changes of the Movement Disorder Society (sponsored revision) of Unified Parkinson's Disease Rating Scale (MDS-UPDRS) endpoint in Parkinson's disease (PD). The data were obtained from Parkinson's Progression Markers Initiative database and included 163,070 observations up to 48 months from 430 subjects belonging to De Novo PD coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 16 publications
3
60
0
Order By: Relevance
“…Future evaluation of the PPMI cohort after more time has passed could help determine whether symptom severity progression continues in a linear manner beyond the first 5 years after diagnosis. However, in support of our results, another recent study reported a linear progression in MDS‐UPDRS scores over time . Gottipati and colleagues studied the PPMI cohort and utilized an Item Response Theory model to determine that a typical participant's MDS‐UPDRS total score (excluding Part IV) increases linearly by 1 standard deviation (estimated at 13.1 points) in 50 months .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Future evaluation of the PPMI cohort after more time has passed could help determine whether symptom severity progression continues in a linear manner beyond the first 5 years after diagnosis. However, in support of our results, another recent study reported a linear progression in MDS‐UPDRS scores over time . Gottipati and colleagues studied the PPMI cohort and utilized an Item Response Theory model to determine that a typical participant's MDS‐UPDRS total score (excluding Part IV) increases linearly by 1 standard deviation (estimated at 13.1 points) in 50 months .…”
Section: Discussionsupporting
confidence: 85%
“…However, in support of our results, another recent study MDS-UPDRS Part III Score (SE) reported a linear progression in MDS-UPDRS scores over time. 19 Gottipati and colleagues studied the PPMI cohort and utilized an Item Response Theory model to determine that a typical participant's MDS-UPDRS total score (excluding Part IV) increases linearly by 1 standard deviation (estimated at 13.1 points) in 50 months. 19 This equates to a change of 3.1 points per year for the MDS-UPDRS total score, which lies close to our estimation using alternate methodology.…”
Section: Discussionmentioning
confidence: 99%
“…the neuronal disability) and therefore, captures more precisely the heterogeneity of the scale (18). Recent publications in the field of central nervous system diseases (19,20) have demonstrated the use of IRT to leverage the information provided by clinical rating scales.…”
Section: Introductionmentioning
confidence: 99%
“…14 The use of IRT as an approach to examine clinimetric properties of the MDS-UPDRS is recent, with methodological variability in the IRT models used, characteristics of PD samples studied, and portions of the scale used in the analyses. Most of these studies use longitudinal data from the Parkinson's Progression Marker initiative, [15][16][17][18] a cohort of early-stage PD patients who do not require treatment at baseline and are followed longitudinally. The majority of these studies applied IRT methods to examine longitudinal change of either total scale scores or unique combinations of different items of the MDS-UPDRS.…”
mentioning
confidence: 99%